Adverse events following immunization of combined diphtheria, whole-cell pertussis, tetanus, and hepatitis B (DPwT/HB) vaccine - Diana Mettadewi Jong; Alan R Tumbelaka; Abdul Latief (Indonesian Pediatric Society, 2004)
Background Combined vaccine of diphtheria, whole-cell pertussis,tetanus, and hepatitis B (DPwT/HB) will reduce the number ofinjections to children and simplify the delivery logistics. The adverseevents following immunization (AEFI) of this vaccine have to beconcerned since the events may increase or decrease.Objectives To evaluate AEFI of DPwT/HB vaccine in healthy in-fants.Methods A descriptive prospective study of AEFI of three dosesof DPwT/HB vaccine was performed on 74 healthy infants agedtwo to six months at the Department of Child Health, CiptoMangunkusumo Hospital, from July 2000 to March 2001.Results Out of 74 infants, 68 received two doses and 67 completedthe study with a total of 209 doses. Of 209 doses, adverse eventswere reported following 126 doses (60.3%), consisted of systemic(60.3%) and local reactions (9.5%). The three most frequent AEFIiwere mild fever (44.5%), high fever (15.7%), irritability (31.5%).Most AEFI were coincidental (51.1%), occurred after more than72 hours (31.4%) and lasted less than 24 hours (17.7%). Sys-temic reactions were mostly found in 4-month-old infants (33.3%),while local reactions in 2-, 3-, and 5-month-old infants (25%),respectively.Conclusion Most AEFI were coincidental and resolved withoutany complication